PENYULUHAN TENTANG KHASIAT BAWANG DAYAK TERHADAP PENYEMBUHAN LUKA DI DESA CANDIREJO - Puji Lestari (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Dayak onion (Eleutherinepalmifolia L.) is a family of iridaceae which contains chemicals in the form of flavonoids, saponins, tannins, alkaloids and steroids which are efficacious to heal wounds.Purpose of this study was to determine the effect of wound healing using onion dayak ethanol extract on white rats, to determine differences in wound healing in white rats given ethanol extract of dayak onion and betadin, and to determine the concentration of dayak onion ethanol extract which was effective in wound healing it's in white mice. Dayak onion extract was obtained from maceration method: Experimental. made a variety of dayak ethanol extract with a concentration of 250 mg / kg BW, 500 mg / kg BW, 750 mg / kg BW. Tests used 25 rats divided into 5 groups: positive control, negative control, ethanol extract onion dayak concentration of 250 mg / kg BW,500 mg / kg BW, 750 mg / kg BW. All rats were slashed in the back area using a bisturic knife 2 cm with a depth of 2 mm. Observation of wounds was carried out every day for 14 days, the length of the wound was measured using a caliper. Data analysis was statistically tested using One Way Anova and continued with the LSD (Least Significany Difference) Results: The statistical results show that the onion ethanol extract has effectiveness in wound healing where the most effective dose is a dose of 750 mg / kg BW with 10 days of wound healing time.